Predictors of Age of Diagnosis and Survival of Alzheimer's Disease in Down Syndrome - Sinai, Amanda; Mokrysz, Claire; Bernal, Jane; Bohnen, Ingrid; Bonell, Simon; Courtenay, Ken; Dodd, Karen; Gazizova, Dina; Hassiotis, Angela; Hillier, Richard; McBrien, Judith; McCarthy, Jane; et al. (Journal of Alzheimer's disease, 2017)
People with Down syndrome (DS) are an ultra-high risk population for Alzheimer's disease (AD). Understanding the factors associated with age of onset and survival in this population could highlight factors associated with modulation of the amyloid cascade. This study aimed to establish the typical age at diagnosis and survival associated with AD in DS and the risk factors associated with these. Data was obtained from the Aging with Down Syndrome and Intellectual Disabilities (ADSID) research database, consisting of data extracted from clinical records of patients seen by Community Intellectual Disability Services (CIDS) in England. Survival times when considering different risk factors were calculated. The mean age of diagnosis was 55.80 years, SD 6.29. Median survival time after diagnosis was 3.78 years, and median age at death was approximately 60 years. Survival time was associated with age of diagnosis, severity of intellectual disability, living status, anti-dementia medication status, and history of epilepsy. Age at diagnosis and treatment status remained predictive of survival time following adjustment. This study provides the best estimate of survival in dementia within the DS population to date, and is in keeping with previous estimates from smaller studies in the DS population. This study provides important estimates and insights into possible predictors of survival and age of diagnosis of AD in adults with DS, which will inform selection of participants for treatment trials in the future.